An automated technique for image noise identification using a simple pattern classification approach - Yixin Chen; Das, M. (2007 50th Midwest Symposium on Circuits and Systems, 2007)
A simple pattern classification based noise identification method is proposed in this paper. The key idea involves isolation of some representative noise samples, and extraction of their statistical features for noise type identification. The isolation of representative noise samples is achieved using simple image filters and noise identification is performed using a few statistical and/or histogram based features. The method seems to be capable of accurately classifying the types of noise studied.